The Practice of the Coexistence of Nations Respectingreligious and Moral Norms - Musayeva, Shahla (Scholarya Demo Journal of Ruby, 2019)
The article reflects author’s research and conclusions on the dangers ofglobalization in the present stage for national and spiritual values, theirdevelopment and global integration.At the same time, some problems concerning the education of youngergeneration are discussed in the article. The author, in this sense, analyzes theresearch of some scholars and attempts to discover the essence of the discussedissues.The factors revealed in the spiritual evolution of humans in theglobalization period are not only of national interest. There are new tendenciesthat coincide with human interests. Relations of human and nature arisecontradictions of which the solution requires serious spiritual relationships.In Azerbaijani society, there are a number of problems that their solutiondepends on both our ideology and strategic plans of our state.We hope that globalization in the Azerbaijani space will not be a dangerousprocess as the state is carrying out domestic and foreign policy with the people.